Pesan Persuasif Menjaring Peluang Investasi dalam Promosi Grand Batang City oleh Kementerian Investasi - Shania Mawardini Priliswari; Imaddudin Imaddudin; Fadli M. Athalarik (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2023)
This study was conducted to determine the process of sending persuasive messages in the promotion activities of Grand Batang City by the Ministry of Investment through the Indonesia Investment Webinar Series 2021 event. The method used in this study is a qualitative method with research subjects consisting of the Ministry of Investment promotion division team, Grand Batang team City and the technical team. Data collection was obtained through interviews, observations and documentation conducted online and offline. The results of this study show that how the process of sending persuasive messages carried out in the Indonesia Investment Webinar Series 2021 event is said to be successful when viewed from how potential investors respond when receiving persuasive messages that have been delivered. Persuasive messages are conveyed with the intention of influencing, inviting and persuading from the rational and emotional side of potential investors with both verbal and non-verbal language so that persuasive messages can be conveyed properly. Although there were obstacles due to the tight timing of the event, the team was able to successfully complete the Indonesia Investment Webinar Series 2021 event well.